Evaluation of the Effectiveness of a Health Promotion Program in Clinical Practice with Elderly Patients - Tiar Erawan; Shanshan Xu; Ismed Ismed; Herlina Lidiyawati; Emdat Suprayitno (Yayasan Adra Karima Hubbi, 2024)
The elderly patient population is vulnerable to various chronic diseases and has limited levels of access to health information. Effective health promotion programs can improve the quality of life of this group and prevent disease. A health promotion program is a series of activities aimed at increasing awareness, knowledge and healthy behaviour in a population or community. This study aims to evaluate the effectiveness of a health promotion program implemented with elderly patients in clinical practice in improving their knowledge, healthy living behaviour and health outcomes. This research method was carried out using a quasi-experimental design using a sample of elderly patients who participated in a six-month health promotion program at a community health clinic. Data collection was carried out through pre- and post-intervention questionnaires, and data analysis was carried out using descriptive statistics and hypothesis testing. The results of this study show an increase in patient knowledge about healthy eating patterns, physical activity, and stress management after participating in the health promotion program. In addition, there have been positive changes in healthy lifestyle behaviour and a reduction in the number of visits to health facilities due to diseases related to unhealthy lifestyles. The conclusion of this research is that health promotion programs for elderly patients in clinical practice are effective in increasing knowledge, improving healthy living behaviour, and reducing the risk of chronic disease. The recommendations of this study are to expand the scope of health promotion programs in various clinical settings and continue to encourage the participation of elderly patients to achieve optimal health outcomes.